Genetics of Vascular Malformations: Current Perspectives - Kin Fon Leong (Wolters Kluwer Medknow Publications, 2021)
For decades, vascular anomalies are categorized as either vascular tumors or malformations based on their onset, clinical course, radiologic, and histologic features. Owing to the heterogeneity of vascular anomalies, they are frequently misdiagnosed. With the advent of massively parallel next-generation sequencing, the molecular landscape of vascular anomalies is rapidly evolving and recent discoveries have shed light on the genetic basis and classification of these vascular disorders. The genotype-phenotype correlation will provide a more precise classification of vascular anomalies and form the basis for future targeted pharmacologic therapy. Thus far, inhibitor of mTOR, AKT1, and PIK3CA (sirolimus, miransertib, and alpelisib) have promising clinical results. In vascular malformations, majority of sporadic cases are due to somatic mutations that disrupt the main endothelial receptor intracellular signaling pathways, i.e., PIK3CA-AKT-mTOR, RAS - MAPK - ERK, and SMAD signaling pathways. Most of the sporadic vascular malformations are caused by somatic mutations that are acquired after fertilization, instead of being inherited from his parents. In general, this type of mosaicism is not inherited, except when the mutation affects the gonads.